APGAR SCORE: COMPARISON OF GENERAL ANAESTHESIA VS SPINAL ANAESTHESIA - ZAHID , B; KHAN, MBA; HANIF, MZ; TAHIR, A; NAZEER , T; KAZMI, SSR (Biological and Clinical Sciences Research Journal, 2023)
Caesarean section is a common obstetric operation performed to save the lives of both the mother and baby. This study aimed to compare the APGAR score of neonates in patients who received general anesthesia or spinal anesthesia during the procedure. For this prospective randomized controlled trial, 160 ASA class I and II patients who underwent elective caesarean section at 37 weeks or more of gestation were selected. The patients were randomly divided into two equal groups, A and B, with 80 patients in each group. Group A received spinal anesthesia with a 25-gauge pain spinal needle using hyperbaric bupivacaine 1.5ml, while Group B received general anesthesia with an endotracheal tube. After the baby’s delivery, the APGAR score was assessed at 1 minute and recorded on a proforma. The results showed that the mean APGAR score at 1 minute in group A was 8.49, while in group B, it was 6.53. The mean age in group A was 30.09 ± 3.35 years, and in group B, it was 29.86 ± 3.16 years. The mean birth weight of neonates in group A was 2999.80 ± 275.78 grams, while in group B, it was 3066.25 ± 281.66 grams.In conclusion, the study found that the APGAR score was better in spinal than in general anesthesia.